Answer

Verified

410.4k+ views

Hint: To prove that the given statement is correct, use induction on \[n\]. Check the validity of the statement for \[n=1\] and then assuming that the statement holds for \[n=k\], prove the statement for \[n=k+1\].

We have the statement that \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\] is divisible by \[512\]. We have to prove this statement. We will do so by using induction on \[n\]. We will check the validity of the given statement for \[n=1\] and then assuming that the statement holds for \[n=k\], we will prove the statement for \[n=k+1\] .

Thus, substituting \[n=1\] in the equation \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\], we get\[{{3}^{2+5}}+160\left( 1 \right)-56\left( 1 \right)-243={{3}^{7}}+160-56-243=2187-139=2048\].

We observe that \[\dfrac{2048}{512}=4\].

Hence, we observe that the statement \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\] is divisible by \[512\] holds for \[n=1\].

We will now prove the statement for \[n=k+1\], assuming that the statement holds for \[n=k\].

As the given statement holds for \[n=k\], we will replace \[n\] by \[k\] in the statement that \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\] is divisible by \[512\].

Replacing \[n\] by \[k\], we get \[{{3}^{2k+5}}+160{{k}^{2}}-56k-243\] is divisible by \[512\].

As \[{{3}^{2k+5}}+160{{k}^{2}}-56k-243\] is divisible by \[512\], we can write it as \[{{3}^{2k+5}}+160{{k}^{2}}-56k-243=512a\], where \[a\] represents some integer.

We will now prove that the statement holds for \[n=k+1\].

Substituting \[n=k+1\]in the expression \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\], we get \[{{3}^{2\left( k+1 \right)+5}}+160{{\left( k+1 \right)}^{2}}-56\left( k+1 \right)-243\].

Simplifying the above expression, we have \[{{3}^{2k+5}}\times 9+160\left( {{k}^{2}}+2k+1 \right)-56k-56-243\].

\[\begin{align}

& \Rightarrow {{3}^{2k+5}}\left( 1+8 \right)+160{{k}^{2}}+160+320k-56k-56-243 \\

& \Rightarrow \left( {{3}^{2k+5}}+160{{k}^{2}}-56k-243 \right)+\left( 8\times {{3}^{2k+5}}+160+320k-56 \right) \\

& \Rightarrow 512a+8\times {{3}^{2k+5}}+104+320k \\

& \Rightarrow 512a+8\left( {{3}^{2k+5}}+40k+13 \right) \\

\end{align}\]

Adding and subtracting the term \[8\left( 160{{k}^{2}}-56k-243 \right)\] from the above expression, we have \[512a+8\left( {{3}^{2k+5}}+160{{k}^{2}}-56k-243-160{{k}^{2}}+56k+243+40k+13 \right)\].

\[\begin{align}

& \Rightarrow 512a+8\left( {{3}^{2k+5}}+160{{k}^{2}}-56k-243 \right)+8\left( -160{{k}^{2}}+96k+256 \right) \\

& \Rightarrow 512a+8\left( 512a \right)-8\times 32\left( 5{{k}^{2}}-3k-8 \right) \\

& \Rightarrow 512b-256\left( 5{{k}^{2}}-3k-8 \right) \\

\end{align}\]

If we substitute \[k=1\] in the above expression, we get \[512b-256\left( -6 \right)=512\left( b+3 \right)=512c\] where \[b\] and \[c\] are some integers.

Thus, we observe that we can write \[512b-256\left( 5{{k}^{2}}-3k-8 \right)=512c\] for integer \[c\].

Hence, we have \[{{3}^{2\left( k+1 \right)+5}}+160{{\left( k+1 \right)}^{2}}-56\left( k+1 \right)-243=512c\] thus, proving that the given statement is true.

Thus, the statement \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\] is divisible by \[512\] holds for all \[n\].

Note: We can also prove this statement by using induction in another way by assuming that the given statement holds for \[n-1\] and then proving it for \[n\].

We have the statement that \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\] is divisible by \[512\]. We have to prove this statement. We will do so by using induction on \[n\]. We will check the validity of the given statement for \[n=1\] and then assuming that the statement holds for \[n=k\], we will prove the statement for \[n=k+1\] .

Thus, substituting \[n=1\] in the equation \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\], we get\[{{3}^{2+5}}+160\left( 1 \right)-56\left( 1 \right)-243={{3}^{7}}+160-56-243=2187-139=2048\].

We observe that \[\dfrac{2048}{512}=4\].

Hence, we observe that the statement \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\] is divisible by \[512\] holds for \[n=1\].

We will now prove the statement for \[n=k+1\], assuming that the statement holds for \[n=k\].

As the given statement holds for \[n=k\], we will replace \[n\] by \[k\] in the statement that \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\] is divisible by \[512\].

Replacing \[n\] by \[k\], we get \[{{3}^{2k+5}}+160{{k}^{2}}-56k-243\] is divisible by \[512\].

As \[{{3}^{2k+5}}+160{{k}^{2}}-56k-243\] is divisible by \[512\], we can write it as \[{{3}^{2k+5}}+160{{k}^{2}}-56k-243=512a\], where \[a\] represents some integer.

We will now prove that the statement holds for \[n=k+1\].

Substituting \[n=k+1\]in the expression \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\], we get \[{{3}^{2\left( k+1 \right)+5}}+160{{\left( k+1 \right)}^{2}}-56\left( k+1 \right)-243\].

Simplifying the above expression, we have \[{{3}^{2k+5}}\times 9+160\left( {{k}^{2}}+2k+1 \right)-56k-56-243\].

\[\begin{align}

& \Rightarrow {{3}^{2k+5}}\left( 1+8 \right)+160{{k}^{2}}+160+320k-56k-56-243 \\

& \Rightarrow \left( {{3}^{2k+5}}+160{{k}^{2}}-56k-243 \right)+\left( 8\times {{3}^{2k+5}}+160+320k-56 \right) \\

& \Rightarrow 512a+8\times {{3}^{2k+5}}+104+320k \\

& \Rightarrow 512a+8\left( {{3}^{2k+5}}+40k+13 \right) \\

\end{align}\]

Adding and subtracting the term \[8\left( 160{{k}^{2}}-56k-243 \right)\] from the above expression, we have \[512a+8\left( {{3}^{2k+5}}+160{{k}^{2}}-56k-243-160{{k}^{2}}+56k+243+40k+13 \right)\].

\[\begin{align}

& \Rightarrow 512a+8\left( {{3}^{2k+5}}+160{{k}^{2}}-56k-243 \right)+8\left( -160{{k}^{2}}+96k+256 \right) \\

& \Rightarrow 512a+8\left( 512a \right)-8\times 32\left( 5{{k}^{2}}-3k-8 \right) \\

& \Rightarrow 512b-256\left( 5{{k}^{2}}-3k-8 \right) \\

\end{align}\]

If we substitute \[k=1\] in the above expression, we get \[512b-256\left( -6 \right)=512\left( b+3 \right)=512c\] where \[b\] and \[c\] are some integers.

Thus, we observe that we can write \[512b-256\left( 5{{k}^{2}}-3k-8 \right)=512c\] for integer \[c\].

Hence, we have \[{{3}^{2\left( k+1 \right)+5}}+160{{\left( k+1 \right)}^{2}}-56\left( k+1 \right)-243=512c\] thus, proving that the given statement is true.

Thus, the statement \[{{3}^{2n+5}}+160{{n}^{2}}-56n-243\] is divisible by \[512\] holds for all \[n\].

Note: We can also prove this statement by using induction in another way by assuming that the given statement holds for \[n-1\] and then proving it for \[n\].

Recently Updated Pages

Basicity of sulphurous acid and sulphuric acid are

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

What is the stopping potential when the metal with class 12 physics JEE_Main

The momentum of a photon is 2 times 10 16gm cmsec Its class 12 physics JEE_Main

Using the following information to help you answer class 12 chemistry CBSE

Why should electric field lines never cross each other class 12 physics CBSE

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

In a cyclic process work done by the system is A Zero class 11 physics CBSE

Give simple chemical tests to distinguish between the class 12 chemistry CBSE

Assertion Fructose is a reducing sugar Reason Fructose class 12 chemistry CBSE

In a cyclic process the amount of heat given to a system class 11 physics CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE